Homestay Tourism as Tourism Development in Pemuteran Traditional Village - Ekawaty, Donna; Julian, Mezi; S.H., M.M, Nanang; Fahreza, Gilang (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2024)
Homestay tourism is an activity in a homestay located in a traditional village environment. Homestay tourism is a special attraction for visiting tourists. Homestay tourism has not been widely utilised by homestay owners and managers. Homestay tourism is a new challenge for residents in meeting the needs of tourists. This is one of the causes of the researcher's interest in conducting research related to Homestay Tourism as a tourism development. The research aims to obtain information on the needs of homestay tourism in facing the challenges of tourism development, contributing to improving the economy of local communities, preserving local culture, preserving local culture and the surrounding environment, and being able to find novelty in the world of hospitality to increase the economic value of local communities. This research uses a qualitative action research method using a problem approach by mapping tourism objects, making observations, and taking documentation of homestay owners and managers. The results of the study show that homestay tourism is capable of standardised tourism development, increasing the economic value of local communities, helping local economic development, and preserving their cultural heritage. The researcher hopes that there will be ongoing and continuous research